The emergence of magazine membership models - Hogarth, Mary (2024)
This article undertakes a comparative analysis of three special interest magazines, Women's Running, Vegan Food and Country Walking, to determine how each title has developed and implemented a membership model. It explores if and how the model has impacted revenue and the audiences while looking for reoccurring themes and examining services. Semi-structured interviews were deemed to be the most appropriate methods by which to conduct this qualitative investigation. Thus, interviews were undertaken with editors and publishers to explore how membership has been established and ascertain the potential impact on revenue and audience engagement. Furthermore, the study reviews key literature themes around servitisation, including work by Viljakainen and Toivonen (2014) and Fließ and Hagenhoff’s (2016) study of membership to establish if the magazines have achieved financial stability and a deeper engagement with their audience.